Linking Primary and Secondary Care after Psychiatric Hospitalization: Comparison between Transitional Case Management Setting and Routine Care for Common Mental Disorders - Bonsack, Charles; Golay, Philippe; Gibellini Manetti, Silvia; Gebel, Sophia; Ferrari, Pascale; Besse, Christine; Favrod, Jérome; Morandi, Stéphane (Frontiers in Psychiatry, 2016)
Objectives. To improve engagement with care and prevent psychiatric readmission, a transitional case management intervention has been established to link with primary and secondary care. The intervention begins during hospitalisation and ends one month after discharge. The goal of this study was to assess the effectiveness of this short intervention in terms of the level of engagement with outpatient care and the rate of readmissions during one year after discharge. Methods. Individuals hospitalised with common mental disorders were randomly assigned to be discharged to routine follow up by private psychiatrists or general practitioners with (n=51) or without (n=51) the addition of a transitional case management intervention. Main outcome measures were number of contacts with outpatient care and rate of readmission during twelve months after discharge. Results. Transitional case management patients reported more contacts with care service in the period between 1 to 3 month after discharge (p = .004). Later after discharge (3-12 month), no significant differences of number of contacts remained. The transitional case management intervention had no statistically significant beneficial impact on the rate of readmission (Hazard ratio = 0.585, p = .114). Conclusions. The focus on follow-up after discharge during hospitalisation leads to an increased short term rate of engagement with ambulatory care despite no differences between the two groups after 3 month of follow-up. This short transitional intervention did however not significantly reduce the rate of readmissions during the first year following discharge. Trial registration number. ClinicalTrials.gov Identifier NCT02258737.